Deixis in Conversation at Kick Andy Metro TV Channel - Nur Ihsan Halil; Retno Susanto (Universitas Sembilanbelas November Kolaka, 2017)
Deixis is a technical term (from the Greek) to one of the fundamental things that we do with speech. Deixis means ‘designation’ through language, when we appoint a foreign object and ask, “apa itu”-“what is it”, then we use the the expression of deixis (“itu”-“it is”) to point something in a context suddenly. The problem in this research is “What Deiksis is contained in Kick Andi's conversation at a dialog of Kick Andy Metro TV”? The goal to be achieved in this research is to describe the Deixis contained in the conversation of Kick Andi at Kick Andy Metro TV show. The benefits in this study theoretically the results in this study is expected to be a source of reference teaching materials with pragmatic subject. Academically, the results of this study can be used as a foothold in examining further pragmatic and Deixis studies in conversations at educational institutions who want to study the language from pragmatic aspects. Practically the results of this study are expected to provide input for the team of curriculum and teachers. For the curriculum team, the pragmatic aspect and the fulfillment of the use of deixis become very important to be included in teaching materials. This research is a type of library research. The method used in this research is descriptive qualitative method. The data in this study are the speeches of the perpetrators containing deixis conversations in broadcast Kick Andy Metro TV. Sources of data in this studvy are conversations Kick Andi dialogue and participants. Data collection techniques in this study is the technique of reading, and note. The data analysis technique used is content analysis. The results show the use of deixis types in conversational dialogues such as (1) deixis of persona, (2) deixis of place, (3) deixis of time, (4) deixis of discourse, and (5) deixis of social.